Changes in proteomic profiles in different prostate lobes of male rats throughout growth and development and aging stages of the life span. Issue 4 (21st August 2012) - Das, Arunangshu; Bortner, James D.; Aliaga, Cesar A.; Baker, Aaron; Stanley, Anne; Stanley, Bruce A.; Kaag, Matthew; Richie, John P.; El‐Bayoumy, Karam
Abstract BACKGROUND Aging‐related changes in important cellular pathways in the prostate may promote a permissive environment for an increased risk for prostatic disease development such as prostate cancer. Our objectives were to examine for such changes, by systematically determining the effects of growth and development and aging on proteomic profiles in different lobes of the rat prostate. METHODS Prostate lobes (dorsolateral lobe, DL and ventral lobe, VL) were obtained from male Fisher rats of various ages representing young (4 months), mature (12 months), old (18 months), and very old (24 months). Differentially expressed proteins between age groups in each lobe were identified using a proteomic approach, isobaric Tags for Relative and Absolute Quantitation (iTRAQ). Select changes in the DL and VL were verified by immunoblot analysis. RESULTS iTRAQ identified 317 proteins with high confidence. iTRAQ discovered 12 and 6 proteins significantly modulated in response to growth and development in the DL and VL, respectively, and 42 and 29 proteins significantly modulated in response to aging in the DL and VL, respectively. Proteins modulated during growth and development in the DL and VL are involved in a variety of biological processes including cell communication and development, whereas proteins modulated during aging were predominantly related to antioxidant activity and immunity. Immunoblot analysis verified age‐related changes for α‐1 antitrypsin, annexin A1, hypoxia up‐regulated protein 1, and 78 kDa glucose‐regulated protein. CONCLUSIONS Aging results in changes in numerous prostatic proteins and pathways which are mainly linked to inflammation and may lead to prostatic disease development. Prostate 73: 363–375, 2013. © 2012 Wiley Periodicals, Inc.